2022
DOI: 10.3390/atmos13040522
|View full text |Cite
|
Sign up to set email alerts
|

Haze Grading Using the Convolutional Neural Networks

Abstract: As an air pollution phenomenon, haze has become one of the focuses of social discussion. Research into the causes and concentration prediction of haze is significant, forming the basis of haze prevention. The inversion of Aerosol Optical Depth (AOD) based on remote sensing satellite imagery can provide a reference for the concentration of major pollutants in a haze, such as PM2.5 concentration and PM10 concentration. This paper used satellite imagery to study haze problems and chose PM2.5, one of the primary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Asongu and Odhiambo (2019) Khan et al (2020) concluded that CO 2 emission has a positive influence on the consumption of traditional energy sources and EG. Adedoyin et al (2020), ), Liu Y. et al (2022, Yin et al (2022) also checked the impact of EG on CO 2 emission and concluded that EG and CO 2 are positively correlated in Asian countries. Anwar et al (2020) examined the effect of coal usage and EG on CO 2 in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Asongu and Odhiambo (2019) Khan et al (2020) concluded that CO 2 emission has a positive influence on the consumption of traditional energy sources and EG. Adedoyin et al (2020), ), Liu Y. et al (2022, Yin et al (2022) also checked the impact of EG on CO 2 emission and concluded that EG and CO 2 are positively correlated in Asian countries. Anwar et al (2020) examined the effect of coal usage and EG on CO 2 in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the proposed traceability system with the traceability system constructed by Yang et al [37], the advantage of the proposed system is that the system solves the problems of asymmetric information, difficult sharing, easy tampering, and centralized storage in the IoT-based agricultural products traceability system of previous researchers, thus making the whole chain of agricultural product information credible and reliable [38][39][40][41][42]. Meanwhile, the proposed system also overcomes the common problems of information storage isolation, data sharing of information systems, and difficult interaction in the traceability of traditional agricultural products [43][44][45][46][47]. e present work takes the resource management problem in computer system and network as the starting point, and understands the difficulties of accurate modeling of existing heuristic methods in complex environments and poor scalability in different environments.…”
Section: Display Of Main Functions Of the Agricultural Product Tracea...mentioning
confidence: 96%
“…In each sampling period, the deep neural network makes predictions for a single data packet obtained by the sensor and sends this data packet to the controller [43][44][45][46][47][48].…”
Section: System Modelmentioning
confidence: 99%